Pengaruh Modal Intelektual dan Pengungkapannya Terhadap Nilai Perusahaan: Efek Intervening Kinerja Perusahaan - Aida, Rahma Nurul; Rahmawati, Evi (Journal of Accounting and Investment, 2015)
The aim of the research is to analyze and to get the empirical prove on the intellectual capital influence which is measured with VAIC and intellectual capital disclosure using Singh and Zahn index (2008) to the company value (EPS) with the company performance (ROE) as intervening variable. The sample of this research is the registered company of Indonesian Stock Market (2011-2013). The first and the second hypotheses were rejected. These may be caused of there was no basic standard to measure the intellectual capital value in Indonesia. The third hypothesis is accepted. The result of the research show that intellectual capital has positive effects to the company values indirectly through company performance as intervening variable. The fourth hypothesis successfully approved that intellectual capital disclosure has positive impact to the company performance. The fifth hypothesis was rejected. It may be caused by the intellectual capital which has not reflected the company value as it is non-salaried. The last hypothesis successfully proved that intellectual capital disclosure affects the company value through the company performance as intervening variable.